Voltammetric determination of copper(II) using antimony film electrodes - Ashrafi, Amir Mansoor; Husáková, Lenka; Vytřas, Karel (Univerzita Pardubice, 2012)
Possibility of determination of Cu(II) at antimony modified carbon paste electrode and its application in determination of trace amount of copper in real sample has been investigated. According to obtained results, it was found that SbF-CPE can be used for these purposes successfully. Both detection limit of 1.45 ppb (evaluated as 3σ) and RSD 4.8 (for 10 ppb Cu and 10 different measurements) were also evaluated. Antimony-based electrodes are environmentally friendly which is their most important advantage rather than mercury-based ones. BiFEs have been used for determination of copper before but because of decrease of the Bi peak with increasing Cu(II) concentration which causes irreproducibility. As known, it was solved by additions of high concentration of a gallium salt or hydrogen peroxide. Using this antimony film electrode, no addition of other chemicals was necessary.
Keywords: antimony film electrode; carbon paste electrode; anodic stripping voltammetry; copper(II) determination